Handgrip strength Is associated with specific aspects of vascular function in individuals with metabolic syndrome (2023)
Background: Metabolic syndrome (MetS) is a disorder associated with an increased risk for the development of diabetes mellitus and its complications. Lower isometric handgrip strength (HGS) is associated with an increased risk of cardiometabolic diseases. However, the association between HGS and arterial stiffness parameters, which are considered the predictors of morbidity and mortality in individuals with MetS, is not well defined. Objective: To determine the association between HGS and HGS asymmetry on components of vascular function in adults with MetS. Methods: We measured handgrip strength normalized to bodyweight (HGS/kg), HGS asymmetry, body composition, blood glucose, lipid profile, blood pressure, pulse wave velocity (PWV), reflection coefficient (RC), augmentation index @75 bpm (AIx@75) and peripheral vascular resistance (PVR) in 55 adults with a diagnosis of MetS between 25 and 54 years old. Results: Mean age was 43.1 7.0 years, 56.3% were females. HGS/kg was negatively correlated with AIx@75 (r = -0.440), p < 0.05, but these associations were not significant after adjusting for age and sex. However, when interaction effects between sex, HGS/kg and age were examined, we observed an inverse relationship between HGS/kg and AIx@75 in the older adults in the sample, whereas in the younger adults, a weak direct association was found. We also found a significant association between HGS asymmetry and PVR (beta = 30, 95% CI = 7.02; 54.2; p <0.012). Conclusions: Our findings suggest that in people with MetS, maintaining muscle strength may have an increasingly important role in older age in the attenuation of age-related increases in AIx@75—a marker of vascular stiffness—and that a higher HGS asymmetry could be associated with a greater vascular resistance.